Social exclusion modulates fairness consideration in the ultimatum game: an ERP study - Qu, Chen; Wang, Yuru; Huang, Yunyun (Frontiers in Human Neuroscience, 2013)
Previous neuroimaging research has identified brain regions activated when people’s fairness consideration changes under conditions of social exclusion. The current study used EEG data to examine the temporal process of changes in fairness consideration under social exclusion. In this study, a Cyberball game was administered to manipulate participants’ social exclusion or inclusion. Then, in the following Ultimatum game, participants’ brain potentials were recorded while they received fair/unfair offers from someone who previously excluded them, someone who previously included them, or a stranger. Results showed that feedback related negativity (FRN) after onset of distribution outcome was more pronounced for unfair offers compared to fair offers. Moreover, the FRN was more negative-going in response to unfair offers from people who previously excluded them than from the includer and the stranger. Fair offers ¬¬¬elicited a larger P300 than unfair offers. In addition, P300 was more positive-going for unfair offers from the stranger than from the excluder and the includer. This study reveals a temporal process in which the effects of social exclusion on fair consideration are reflected in FRN in the early stage of outcome evaluation. These data also suggest that the FRN is modulated by the subjective evaluation of outcome events in a social context.